The Effect of Application Features, Service Quality and Price on the Frequency of Use of Maxim Online Transportation Services in Islamic Business - Andriani, Riski; Iqbal, Muhammad; Susanto, Is (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to evaluate and identify the features of the Maxim application, as well as service quality and explore prices that can increase the frequency of Use Of Maxim transportation services in Bandar Lampung. The method used is a questionnaire with a total of 100 respondents randomly selected or randomly selected from the city of Bandar Lampung. This study is quantitative. The data analysis technique used in this study is PLS (Partial Least Square) using SmartPLS 3.0 software. Based on the results of hypothesis tests that have been carried out, the application of these features proved to have no positive and significant effect on frequency. Where the direct effect test showed insignificant results of 0.847 and reached 0.05. while the Quality of Service has been shown to have a positive and significant effect on frequency. Where the direct effect test showed significant results of 0.000 and did not reach 0.05. And Price was shown to have a positive and significant influence on frequency. Where the direct effect test showed significant results of 0.009 and did not reach 0.05. In the Islamic perspective, frequency is not only measured by productivity, but also by spiritual values such as trust, responsibility, fairness, honesty, transparency, and customer satisfaction. The integrity of modern technology, such as app features, quality of Service, and Islamic-based pricing, can create a more equitable, transparent, and sustainable business environment. By implementing Islamic values in the development and operation of technology, service providers can increase user trust, satisfaction, and loyalty, as well as provide a positive impact on society as a whole in the city of Bandar Lampung.